2019
DOI: 10.2217/fon-2019-0007
|View full text |Cite
|
Sign up to set email alerts
|

Survival Nomogram for Patients with Initially Diagnosed Metastatic Non-Small-Cell Lung Cancer: A SEER-Based Study

Abstract: Aim: Prognosis of patients with metastatic non-small-cell lung cancer differ widely. Methods: All patients were randomly divided into training or validation cohort. Cox-regression analyses were conducted to select independent predictors. We built a nomogram by R code and evaluated the accuracy and the reliability of the model using C-index, calibration curves and decision curve analyses. We made a risk classification system based on the nomogram. Results: In the validation cohort, C-index was 0.729 and 0.738 f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
18
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 31 publications
9
18
1
1
Order By: Relevance
“…In our new established model, it is clear that AJCC stage and surgery have a significant impact on the total score used for predicting the outcomes of elderly SCC patients. These findings were similar with previous reports, it was observed that metastatic location and pathological grading were crucial independent predictors for OS in NSCLC [26]. Some studies discovered that chemotherapy, metastasis and surgery made the larger contribution to the prognosis for distantly metastatic non-small-cell lung cancer [27,28].…”
Section: Discussionsupporting
confidence: 92%
“…In our new established model, it is clear that AJCC stage and surgery have a significant impact on the total score used for predicting the outcomes of elderly SCC patients. These findings were similar with previous reports, it was observed that metastatic location and pathological grading were crucial independent predictors for OS in NSCLC [26]. Some studies discovered that chemotherapy, metastasis and surgery made the larger contribution to the prognosis for distantly metastatic non-small-cell lung cancer [27,28].…”
Section: Discussionsupporting
confidence: 92%
“…Our study found that the overall incidence of UTUC decreased slightly between 1988 and 2015, which may be due to in the article by Munoz et al used 1980 US standard population (21,526,796) as a standardized, while we used the 2000 US standard population (26,787,544) as a standardized, resulting in a lower overall incidence than Munoz et al We speculate that the difference between our results and Raman et al due to the impact of different databases used.…”
Section: Discussioncontrasting
confidence: 56%
“…[20] The nomogram is a visual tool for predicting prognosis based on multiple variables. [21] The model integrates a variety of prognostic factors and can make more preparations for evaluating the survival possibility of individual patients. [22] At present, many cancer nomograms have been developed and…”
Section: Discussionmentioning
confidence: 99%
“…According to our study, tumor size is a significant factor affecting the patient prognosis, which has not been recognized previously [11][12][13]. T stage roughly classifies tumor size or depth of invasion, but it cannot reflect the specific character of NSCLC patients with BM and accurately predict the prognosis, because the tumor size of the same period varies greatly [23][24][25].…”
Section: Discussionmentioning
confidence: 63%
“…More importantly, many other factors should be considered and involved in predicting the prognosis of patients [9,10]. Survival prediction models designed for lung cancer with BM specifically have been reported previously [11][12][13]. However, the performance of these models is barely satisfactory as these models are based on the simple Cox regression model but not established as a survival prediction model for NSCLC with BM particularly.…”
Section: Introductionmentioning
confidence: 99%